Pembangunan Inklusif dan Industrialisasi di Indonesia: Dampaknya terhadap Kesejahteraan - Setiawan, Avi Budi; Prasetyo, Farhan Hadi; Yusuf, Mochammad; Prajanti, Sucihatiningsih Dian Wisika; Bowo, Prasetyo Ari; Fafurida, Fafurida (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
Indonesia has an economic transformation. However, it tends to experience deindustrialization and development inclusivity challenges. This research examines the influence of industrialization and inclusivity to improve welfare in the short and long term. The analytical method is Autoregressive Distributed Lag, using province-level panel data from 2012–2021. Based on results, industrialization has not significantly affected welfare improvement in the short term. Inclusivity has no significant impact in the short term, but it has a negative direction. However, in the long term, industrialization and inclusivity positively and significantly increase welfare. This confirms that industrialization and inclusivity require time to create welfare.